Tinjauan Hukum Atas Pemberesan dan Pembagian Harta Pailit Oleh Kurator: Studi Kasus PT. Yama Engineering Berdasarkan Putusan Pengadilan Niaga Jakarta Pusat - Narindra, Rochella Amalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the mechanism of settlement and distribution of bankrupt assets by the curator, based on the Decision of the Central Jakarta Commercial Court in the bankruptcy case of PT. Yama Engineering. The main focus is a legal analysis of the curator's implementation of duties in managing the bankruptcy estate and distributing liquidation proceeds to creditors in accordance with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The results indicate that although the curator acted in compliance with legal procedures, substantial inequality emerged in the distribution due to the limited value of bankrupt assets and high settlement costs. Secured creditors received prioritized payments, while preferred creditors such as workers and the state only recovered a small portion of their claims. Concurrent creditors received nothing. These findings highlight the need to reform the bankruptcy system to ensure substantive justice for all parties involved.